2004
DOI: 10.1116/1.1667509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dislocations on luminescence properties of silicon-doped GaN grown by metalorganic chemical vapor deposition method

Abstract: Articles you may be interested inEffect of indium surfactant on stress relaxation by V-defect formation in GaN epilayers grown by metalorganic chemical vapor deposition J. Appl. Phys. 108, 093511 (2010); 10.1063/1.3487955 Erratum: "Elimination of nonuniformities in thick GaN films using metalorganic chemical vapor deposited GaN templates" [J. Elimination of nonuniformities in thick GaN films using metalorganic chemical vapor deposited GaN templates J. Appl. Phys. 90, 6011 (2001); 10.1063/1.1415363 Effect of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Reynolds et al found that the PL peak position in n-type GaN varied very little, which was attributed to the combined effect of screening that produces a blueshift and band gap renormalization that produces a redshift in the optical transitions. 30) Whereas, Yoshikawa et al 32) and Alam et al 33) found that with increasing Si doping concentration, the PL peak position was first redshifted and then blueshifted at above the critical doping concentration. This blueshift at high doping concentration was attributed to the band filling effect 32) or a redistribution of the dislocation density due to strain relaxation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Reynolds et al found that the PL peak position in n-type GaN varied very little, which was attributed to the combined effect of screening that produces a blueshift and band gap renormalization that produces a redshift in the optical transitions. 30) Whereas, Yoshikawa et al 32) and Alam et al 33) found that with increasing Si doping concentration, the PL peak position was first redshifted and then blueshifted at above the critical doping concentration. This blueshift at high doping concentration was attributed to the band filling effect 32) or a redistribution of the dislocation density due to strain relaxation.…”
Section: Resultsmentioning
confidence: 97%
“…This blueshift at high doping concentration was attributed to the band filling effect 32) or a redistribution of the dislocation density due to strain relaxation. 33) Which mechanism dominates in the PL spectra of Si doped a-plane GaN is unclear for now and further investigation is in progress.…”
Section: Resultsmentioning
confidence: 99%
“…This broadening of the FWHM is expected as a result of high carrier concentration (at the low-energy side) introduced by Si impurities compared to undoped GaN and it can be explained by the tailing of the density of states caused by potential fluctuations introduced by the random distribution of Si dopants 39 . In addition, residual acceptors may contribute to the NBE peak broadening in the same way by introducing potential fluctuations 40 . Intensity power dependence studies show that decreasing the excitation intensity by three orders of magnitude produces no significant changes in the observed PL spectra, indicating that no band-gap filling or saturation of the defect level occurs and suggesting that these effects do not contribute to the broadening 41 .…”
Section: Resultsmentioning
confidence: 99%
“…N edge was found to be about an order of magnitude higher than N screw . Reduction in N edge at N Si Ͼ 5 ϫ 10 18 cm −3 could be due to the bending and annihilation of these dislocations 16,23 to accommodate for the change in tensile stress ͓see Fig. 1͑b͔͒.…”
mentioning
confidence: 99%